1991
DOI: 10.1063/1.105855
|View full text |Cite
|
Sign up to set email alerts
|

Electron-cyclotron-resonance plasma-enhanced chemical vapor deposition of epitaxial Si without substrate heating by ultraclean processing

Abstract: By Ar plasma-enhanced decomposition of SiH4 using ultraclean electron-cyclotron-resonance plasma processing, low-temperature Si epitaxy has been achieved even without external substrate heating for the first time. Ar plasma pre-exposure experiments have revealed that Ar ion energies lower than a few eV are favorable for Si epitaxy at low temperatures, in order to suppress plasma damage on the surface crystallinity. Furthermore, it has been found that addition of H2 to the Ar plasma is extremely effective to re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

1994
1994
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(7 citation statements)
references
References 10 publications
0
6
1
Order By: Relevance
“…We have also found that a hydrogen plasma pre-treatment before film growth is not necessary to get epitaxial film growth. This is different from the results reported by [15][16][17]. Epitaxial growth was observed at temperatures as low as 470'C on silicon.…”
Section: Effects Of Thermal Annealingcontrasting
confidence: 83%
“…We have also found that a hydrogen plasma pre-treatment before film growth is not necessary to get epitaxial film growth. This is different from the results reported by [15][16][17]. Epitaxial growth was observed at temperatures as low as 470'C on silicon.…”
Section: Effects Of Thermal Annealingcontrasting
confidence: 83%
“…This can be possibly done by increasing the roughness of the substrate by etching so that the “critical” peak-to-valley height of the seeding layer can be earlier achieved. It is important to point out, that, owning to the widespread use of the plasma enhanced CVD technique in the synthesis of various materials featuring a close-packed structure45464748, the approach shown here is not only limited to the fabrication of 3C-SiC NSs arrays, but also applicable to other materials such as diamond45, Si46, ZnO47, and cubic BN48 etc. The 3C-SiC NSs obtained in the present study are of great scientific importance on their own.…”
Section: Discussionmentioning
confidence: 99%
“…Epitaxial growth of relaxed Ge buffer and strained Si was performed using an ultraclean ECR Ar plasma enhanced CVD system without substrate heating [4][5][6][7]. The system is shown schematically in figure 1.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, in our previous work, it has been clarified that plasma process is a very effective method for lowering deposition temperature, e.g. Si epitaxial growth on Si(1 0 0) [4,5], Ge epitaxial growth on Si(1 0 0) with a flat surface [6,7] and thermal stability of strained Ge [7] using ECR plasma CVD without substrate heating. Especially, we obtained a thinner Ge film with almost a strain-free and flat surface on Si(1 0 0) [7].…”
Section: Introductionmentioning
confidence: 99%